Pengaruh Model Make A Match Pada Materi Satuan Waktu Terhadap Hasil Belajar Siswa Kelas III Sekolah Dasar - Mardalena, Nanda; Heryanto, A.; Sunedi, Sunedi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to determine the effect of the make a match model on the unit of time material on the learning outcomes of grade III elementary school students. The research method used in this research is Quasi Experimental Design with posttest only control design type with a total sample of 33 students. The sample in this study was taken using cluster random sampling technique where the entire population was used as a sample in a way where the researcher divided the population into several groups for research. The data collection technique used is an essay test totaling 10 questions. Based on the research results from the final results of the experimental class data, the experimental class has a higher average value than the lower control class, namely the experimental class value of 81.25 while the control class is 65.63. With a sig value (2-tailed) of 0.018 and t table of 0.05, the sig value. (2-tailed) < t table or 0.018 < 0.05. This means that there is an effect of the make a match model on the unit of time material on the learning outcomes of third grade elementary school students.